THE INFLUENCE OF FINANCIAL LITERACY ON THE FINANCIAL MANAGEMENT BEHAVIOR OF UNIVERSITY STUDENTS AUGUST 17, 1945 JAKARTA - PUSPITA DEWI, WINDA; Manurung, Harris (JOURNAL OF BUSINESS STUDIES, 2023)
Financial literacy is a combination of awareness, knowledge, skills, attitudes and behaviors that a person needs to possess to make sound financial decisions and ultimately achieve individual financial well-being. The purpose of this study is to determine the picture of financial literacy and financial management behavior in students, as well as to determine the influence of financial literacy on student financial management. The study used quantitative research methods. The results of data collection through questionnaires were then processed using SPSS and analyzed using multiple linear regression statistical methods. Based on this, it was found that financial literacy with indicators of basic financial knowledge, savings and loans affected student financial management, while insurance and investment did not affect student financial management.